Sitografia - Siemoneit, Johannes Gabriel (Artes Renascentes)

Rewiring the aging brain: exergaming modulates brain complexity in older adults - Piskin, Daghan Yüksel; Müller, Helen Martha; Skjæret-Maroni, Nina; Vereijken, Beatrix; Baumeister, Jochen (Frontiers in Aging Neuroscience)
Introduction Age-related changes in brain signal complexity are associated with cognitive decline and reduced neural adaptivity in older adults. Exergaming offers a promising prophylactic intervention combining physical and cognitive training. The aim of the present study was to assess how exergaming alters the temporal trajectory of brain signal complexity at rest and during gameplay in older adults. Methods Twenty-eight healthy older adults participated in a 4-week exergaming intervention. Electroencephalography was recorded using 64 electrodes at rest (pre- and post-intervention) and during exergaming (pre-, mid-, and post-intervention). Brain signal complexity was quantified using multiscale entropy across 64 time scales on preprocessed signals. Results Post-intervention resting-state analysis revealed significant reductions at fine and increases at coarse scales in frontal, central, and posterior entropy. During gameplay, entropy declined widespread by mid-intervention, particularly at coarse scales over frontal, central and temporal regions. From mid- to post-intervention, the decline narrowed leaving a net pre-to-post reduction concentrated at coarse scales in these regions. Discussion Resting-state changes indicated a shift toward a younger brain profile, characterized by a transition from age-related increases in local processing to enhanced distributed processing, which may potentially mitigate the rise in neural modularity associated with aging. During gameplay, brain signal complexity decreased in week 2, followed by a modest change by week 4, consistent with the framework in which complexity initially streamlines and then adjusts toward a task-specific optimum. These findings suggest that exergaming can beneficially modulate brain complexity in older adults, offering the potential to reduce age-related neural decline and support healthy brain aging.

Thermodynamic Properties of Tetramethoxysilane - Fiedler, F.; Baumhögger, Elmar; Kruse, Simon; Lemmon, E. W.; Kasper, Tina; Thol, M. (International Journal of Thermophysics)
Abstract A fundamental equation of state for tetramethoxysilane (TMOS) is developed based on the available experimental data. In addition, new density and speed of sound measurements were performed specifically for this work to improve the database. Owing to the limited overall data set, additional thermodynamic properties were analyzed to support the fitting procedure and ensure physically consistent behavior. Modified representations of thermodynamic properties that are typically employed in the fitting procedure were introduced to facilitate the application of constraints. The resulting model provides a consistent description of the thermodynamic properties of TMOS.

Vom Hühner-Holocaust über die Öko-Diktatur zum Kulturkampf um die Currywurst. Korpuslinguistische Perspektiven auf ernährungsbezogene Politisierungen - Markewitz, Friedrich; Wilk, Nicole M. (Zeitschrift für Literaturwissenschaft undLinguistik)

Brain complexity in motion: Multiscale entropy analysis on mobile EEG data to assess motor performance - Piskin, Daghan Yüksel; Cobani, Gjergji; Büchel, Daniel; Lehmann, Tim; Baumeister, Jochen (Brain Research Bulletin)

Zu Verbotenen Texten im Nationalsozialismus - Markewitz, Friedrich (Aptum. Zeitschrift für Sprachkritik und Sprachkultur)

Kommunikative Strategien im Umgang mit Macht und Ohnmacht im Getto Litzmannstadt - Markewitz, Friedrich (Macht und Partizipation in gesellschaftlichen Transformationsprozessen)

120 Tage im 'SS Experiment Love Camp'. Zu Genretropen und -kontroversen im Nazisploitationfilm - Markewitz, Friedrich (Pop-Zeitschrift)

Art the Clown goes to Hollywood. Wenn transgressives Genrekino Mainstream wird - Markewitz, Friedrich (Pop-Zeitschrift)

Hardness of approximation for ground state problems - Gharibian, Sevag; Hecht, Carsten (51st International Symposium on Mathematical Foundations of Computer Science (MFCS))
After nearly two decades of research, the question of a quantum PCP theorem for quantum Constraint Satisfaction Problems (CSPs) remains wide open. As a result, proving QMA-hardness of approximation for ground state energy estimation has remained elusive. Recently, it was shown [Bittel, Gharibian, Kliesch, CCC 2023] that a natural problem involving variational quantum circuits is QCMA-hard to approximate within ratio N^(1-eps) for any eps > 0 and N the input size. Unfortunately, this problem was not related to quantum CSPs, leaving the question of hardness of approximation for quantum CSPs open. In this work, we show that if instead of focusing on ground state energies, one considers computing properties of the ground space, QCMA-hardness of computing ground space properties can be shown. In particular, we show that it is (1) QCMA-complete within ratio N^(1-eps) to approximate the Ground State Connectivity problem (GSCON), and (2) QCMA-hard within the same ratio to estimate the amount of entanglement of a local Hamiltonian's ground state, denoted Ground State Entanglement (GSE). As a bonus, a simplification of our construction yields NP-completeness of approximation for a natural k-SAT reconfiguration problem, to be contrasted with the recent PCP-based PSPACE hardness of approximation results for a different definition of k-SAT reconfiguration [Karthik C.S. and Manurangsi, 2023, and Hirahara, Ohsaka, STOC 2024].

(Nicht)Nutzung von KI-Werkzeugen in der Lehre: ein Reflexionspapier - Rohlfing, Katharina J.; Steinhardt, Isabel; Scharlau, Ingrid; Schaper, Niclas; Holtfreter, Susan; Biere, Lea; Grimminger, Angela; Schmidt, Rebecca; Festner, Dagmar Franziska; Schmidt, Rebekka; Buhl, Heike M.; Mindt, Ilka; et al.

Ein Format zur handlungsnäheren Prüfung von Unterrichtsplanungskompetenz für das Lehramtsstudium im Fach Physik - Vogelsang, Christoph; Riese, Josef (Handlungsorientierung in der Ausbildung von Lehrkräften und pädagogischen Fachkräften. Konzeptionen und Forschungsperspektiven)

Towards Stakeholder-Aware Demand-Side management assessment in heterogeneous residential Microgrids: A Multi-Agent approach - Henne, Kevin; Rahlf, Henning Christoph; Naumann, Marius; Meschede, Henning (Energy Conversion and Management: X)
Expanding renewable energy sources is essential for a sustainable energy supply but challenges grid stability, as the volatility of solar and wind causes periods of over- and undersupply. Private households are central to this transition, combining dynamic consumption with decentralised generation. This paper presents a multi-agent microgrid simulation built on the Mesa framework, focusing on the heterogeneous objectives and technological capabilities of residential participants. Households are modelled as autonomous agents with individual strategies, while a dedicated “grid agent” represents the distribution system operator and regulates the microgrid in a grid-supportive manner. The emission factor serves as the key indicator for grid-friendly behaviour. Results show that in summer, unmanaged PV feed-in from heterogeneous households causes substantial grid stress and balancing effort for the distribution system operator. Dynamic electricity prices can incentivise grid-friendly dispatch, but their effectiveness depends on the correlation between price signals and renewable availability and cannot guarantee grid-supportive behaviour alone. The grid agent reliably improves the grid-supportive coefficient, yet its operating strategy, for instance additional peak-reduction objectives, can interfere with price-based incentives. Effective demand-side management therefore requires careful analysis of stakeholder interactions. Building on this insight, thepaper provides a basic framework for the design, implementation, and assessment of both integrated and individual energy management strategies within a microgrid environment. By simulating the dynamic interactions among system participants and strategies, it enables comprehensive evaluation of their collective impact on the grid, supporting the development of robust solutions for future electricity networks.
Keywords: Microgrid; Decentralised Energy Systems; Multi-Agent System; Residential Demand-Side Management; Optimisation

Optimization of Site-wide Heat-Integrated Utility Systems with Heat Pumps using MILP - Hochhaus, Thorben; Grünewald, Marcus; Riese, Julia (Systems and Control Transactions)
The reduction of CO2-emissions in the chemical industry is essential to meet European climate targets. Particularly, the reliance on fossil fuels for process heat supply is a key factor for CO2-emissions. Electrically driven compression heat pumps are a promising option to reduce fossil fuel consumption by upgrading low-temperature waste heat to a higher temperature level, provided that low-carbon electricity is available. However, the integration of heat pumps into chemical utility systems remains a challenge due to economic constraints and the high complexity associated with site-wide heat integration and retrofit of existing structures. This work presents a mixed-integer linear programming (MILP) approach for the optimization of utility systems with integrated heat pumps. To address computational complexity, candidate utility temperature levels are pre-selected, and feasible heat pump coefficients of performance (COP) are precomputed. The framework is applied to both greenfield and retrofit scenarios for a synthetic case study consisting of 400 process streams. In the greenfield scenario, optimal utility temperature levels and heat pump integration configurations are identified. For the retrofit scenario, temperature levels of an existing utility system are modified to reduce total annual costs (TAC). Additionally, sensitivity analysis is conducted to assess the influence of key economic and environmental parameters. The presented case studies demonstrate short solution times, highlighting the suitability of the proposed framework for screening studies and systematic sensitivity analyses in early-stage design and retrofit applications.

Development of a methodology for heat pump-based heat integration in batch processes - Wloch, Johannes; Grünewald, Marcus; Riese, Julia (Systems and Control Transactions)
Heat pumps offer the possibility of reducing CO2-emissions in the chemical industry. However, the integration of heat pumps, especially in non-continuous processes, faces several challenges. Energy storage facilitates a way to enhance heat integration by providing a continuous supply of heat flows. By doing so, the question arises as to whether this implementation should be applied to the process or to the utility level. At the process level, there is usually more freedom, as one is not bound by the existing temperature levels of the utility system, which are mostly difficult to retrofit. Therefore, this study presents an approach that generates heat integration concepts at the process level based on two different criteria. These criteria influence which process streams are grouped for a storage implementation and therefore influence the heat integration. The aim is to maintain the heat flows as continuous as possible by integrated heat storages. Finally, the possible heat integration concept is evaluated in terms of energy efficiency by a know method for continuous process streams, here the pinch analysis.

Der Logarithmus zur Bestimmung des pH-Wert-Verlaufs einer Titration: Ein fächerverbindender Unterrichtsvorschlag unter Verwendung digitaler Werkzeuge - Bender, Roland; Witte, Thomas; Hattermann, Matthias; Fechner, Sabine (Neue Materialien für einen realitätsbezogenen Mathematikunterricht)

Forum Psychomotorik: Bewegung, Spiel und Sport im schulischen Ganztag - Satzinger, Nicole; Noetzel, Ida (Motorik)

Cost of debt for private firms revisited: voluntary audits as a reflection of risk - Ichev, Riste; Koren, Jernej; Kosi, Urska; Sitar Sustar, Katarina; Valentincic, Aljosa (International Review of Economics & Finance)
We examine the relation between voluntary audit and the cost of debt in private firms. We use a sample of 7420 small private firms operating in the period 2006-2022 that are not subject to mandatory audits. Firms self-select into voluntary audits because of the economic setting (e.g., ownership complexity, export, subsidiary status) or because firm fundamentals limit their access to financial debt. In the outcome analyses, we find that voluntary audits result in higher, rather than lower, interest rates with increases ranging from approximately 1.7 percentage points, but going higher depending on the exact specification. This effect is present regardless of the perceived audit quality (Big-4 vs. non-Big-4), consistent across auditor types. Audited firms’ earnings are less informative about future operating performance. Voluntary audits facilitate access to financial debt for high-risk firms. The price paid is reflected in higher interest rates for voluntary audits – firms with higher information/fundamental risk.

The Role of Stakeholders in CSR Reporting of Non-Listed Banks - Gulenko, Maryna; Kohlhase, Saskia; Kosi, Urska (Accounting in Europe)
We investigate the role of stakeholders in the CSR reporting of non-listed savings banks in Germany. They are established by municipal trustees and serve clients in their distinct operating area. Reporting discretion under the Non-Financial Reporting Directive may lead to variation in CSR reporting due to differences in sustainability interests of banks’ stakeholders and CSR governance (e.g. existence of a CSR manager). We document that the CSR reports and specific CSR dimensions are intensely associated with the existence of strong CSR governance and to a lesser extent with the interests of municipal trustees and bank clients. However, the associations with these stakeholders are predominantly present in banks with strong CSR governance. Our findings inform policy discussions about detailed CSR disclosure requirements (e.g. the European Sustainability Reporting Standards) and extension of reporting scope to firms with regional orientation and absence of typical shareholders.

"Kirchentag" - An example of religious happenings as places for the formation of faith in a world full of diversity - Schroeter-Wittke, Harald (Religious Diversity and Global Concerns)